1995
DOI: 10.1097/00006676-199507000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Essential Fatty Acid Deficiency Prevents Autoimmune Diabetes in Nonobese Diabetic Mice Through a Positive Impact on Antigen-Presenting Cells and Th2 Lymphocytes

Abstract: Protective effects of essential fatty acid deficiency (EFAD) on autoimmunity were shown in rodents. Our goal was to investigate the mechanisms of EFAD effects on autoimmune diabetes in nonobese diabetic (NOD) mice. Weanling female mice were randomized between a control diet group and an EFAD diet group, and the development of diabetes and immune response was determined over a 6-month period. The cumulative incidence of diabetes was significantly reduced in the EFAD group (20 vs 68.75% in the control group; p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…For example, it has been shown that deficient internalization of AC by Mfs derived from diabetic individuals is accompanied by decreased production of IL-10 and increased secretion of pro-inflammatory cytokines, generating an unusual pro-inflammatory environment in response to AC (O'Brien et al 2006;Trudeau et al 2000;Marée et al 2008;Mohammad et al 2006). On the contrary, incubation of DMT1-derived Mfs with pro-inflammatory stimuli has been shown to produce unusually high levels of PGE 2 , which leads to down-regulation of cellular immune activation and therefore a decrease in inflammation (Benhamou et al 1995). Clinically, DMT1 patients are more susceptible to the development of recurrent and more severe infections than non-diabetic individuals (Pozzilli and Leslie 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that deficient internalization of AC by Mfs derived from diabetic individuals is accompanied by decreased production of IL-10 and increased secretion of pro-inflammatory cytokines, generating an unusual pro-inflammatory environment in response to AC (O'Brien et al 2006;Trudeau et al 2000;Marée et al 2008;Mohammad et al 2006). On the contrary, incubation of DMT1-derived Mfs with pro-inflammatory stimuli has been shown to produce unusually high levels of PGE 2 , which leads to down-regulation of cellular immune activation and therefore a decrease in inflammation (Benhamou et al 1995). Clinically, DMT1 patients are more susceptible to the development of recurrent and more severe infections than non-diabetic individuals (Pozzilli and Leslie 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that heightened prostaglandin (PG) metabolism by macrophages may contribute to non-MHC-encoded APC dysfunction (20)(21)(22). PGs are lipid molecules derived from arachidonic acid; the ratelimiting step in their production is mediated by the cyclooxygenase PG synthase (PGS) (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…At first glance, enhanced prostanoid production in the NOD mouse would appear to be beneficial, as PGE 2 promotes Th2 responses in vitro (34,35,37) and suppresses IL-12 production (39), both of which are associated with protection from diabetes in the NOD mouse (40)(41)(42). However, reducing macrophage PGE 2 production in vivo, either by dietary fatty acid manipulation (22) or by treating NOD mice with indomethacin to block cyclooxygenase activity, significantly reduces diabetes incidence in female NOD mice by 70% and 50%, respectively (X.T. Xie, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Since arthritis starts to escalate near day 14, it was reasoned that 2 wk of feeding prior to the arthritic escalation would be sufficient to reach a steady-state level of AA in plasma and inflammatory cells. During the period of maximal arthritic escalation (days [14][15][16][17][18][19][20][21][22][23][24][25], the AA would then be used as a substrate for the synthesis of proinflammatory eicosanoids. The 1× human daily equivalent of AA was insufficient to restore the plasma level of AA to that of the chow control group (Fig.…”
Section: Discussionmentioning
confidence: 99%